Design And Analysis Of Cmos RFIC If Lowpass Filter 1.9GHz Range For CDMA Applications - Loo, Kwang Tatt (Universiti Sains Malaysia, 2005)
This research sets out to design a completely integrated tunable low pass filter (LPF) with a bandwidth of 200 MHz utilizing Silterra 0.18μm submicron (SM) complementary metal oxide semiconductor (CMOS) technology. The application of this filter is narrowed down to perform as an IF filter in a superheterodyne receiver. Currently there are a few reported examples of this type of fully integrated CMOS filter. The main goals in the research will be to design and analyze the various types of filter architecture construction and choose one of the best of them to implement on integrated circuit layout base on their performance.